Hierarchical Reinforcement Learning in Complex Learning Problems: A Survey - Mahajan, Samiksha (International Journal of Computer Sciences and Engineering, 2014)
Reinforcement Learning (RL) is an active research area of machine learning research based on the mechanism of learning from rewards. RL has been applied successfully to variety of tasks and works well for relatively small problems, but as the complexity grows, standard RL methods become increasingly inefficient due to large state spaces. This paper surveys Hierarchical Reinforcement Learning (HRL) as one of the alternative approaches to cope with issues regarding complex problems and increasing the efficiency of reinforcement learning. HRL is the subfield of RL that deals with the discovery and/or exploitation of underlying structure of a complex problem and solving it using reinforcement learning by breaking it up into smaller sub-problems. This paper gives an introduction to HRL, discusses its basic concepts, different algorithms, approaches and related work regarding Hierarchical Reinforcement Learning. At last but not the least this paper briefly gives variation between flat RL and HRL following its pros and cons. It concludes with research scope of HRL in complex problems.